Effects of a Resilience Intervention Within a Nurse Residency Program - Alexandra M. Miller; Arissa Tee; Nicholas A. Giordano; Carrie Mcdermott; Jack Hudson; Ingrid M. Duva (Journal of Advanced Nursing, 2026)
ABSTRACT Aims To evaluate resilience, burnout, intent to leave and use of resiliency skills among new graduate nurses following the introduction of resiliency skills during a nurse residency programme. Design This programme evaluation used a quasi‐experimental, repeated‐measures design, with assessments conducted at baseline, 2 weeks and 3 months following the intervention. Methods Nurse residents participated in a 1‐h, in‐person introduction to the evidence‐based Community Resiliency Model (CRM) as part of a didactic day away from bedside care. The CRM is a sensory‐focused self‐care approach to regulating the nervous system and is associated with improved healthcare worker well‐being and work team engagement. Changes in resilience and burnout were evaluated over time, and relationships among resiliency skill use, resilience, burnout and intent to leave were examined. Results The training was well received based on post‐intervention surveys. A total of 135 nurse residents were trained, and 68 provided evaluation data at baseline and 3 months. No significant changes in resilience, burnout or intent to leave scores were observed. However, 73% of new graduate nurse participants reported using the resiliency skills at least once during the 3 months following training. Conclusion This evaluation suggests that the CRM training is feasible and acceptable as an addition to new graduate nurse professional development strategies. Although no significant changes in resilience, burnout or intent to leave were observed, the majority of participants reported using resiliency skills following training. Introducing sensory‐based resiliency skills during the residency period may provide nurses with practical strategies for managing role transition and work‐related stress that can be reinforced and further developed throughout their careers.